2019
DOI: 10.3390/ijms20236018
|View full text |Cite
|
Sign up to set email alerts
|

Human Recombinant Arginase I [HuArgI (Co)-PEG5000]-Induced Arginine Depletion Inhibits Colorectal Cancer Cell Migration and Invasion

Abstract: Purpose: Colorectal cancer (CRC) is the third most common type of cancer worldwide, and it represents over half of all gastrointestinal cancer deaths. Knowing that cancer cells have a high proliferation rate, they require high amounts of amino acids, including arginine. In addition, several tumor types have been shown to downregulate ASS-1 expression, becoming auxotrophic for arginine. Therefore, Arginine deprivation is one of the promising therapeutic approaches to target cancer cells. This can be achieved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 49 publications
7
58
0
Order By: Relevance
“…Arginine is essential for protein synthesis in adult mammals and plays multiple functions in cell activities. Based on the metabolic vulnerability in tumors, arginine deprivation therapies were developed recently through giving availability to arginine degrading enzymes 18 . In the present study, arginine in mice serum was down-regulated suggesting that the impairment in arginine synthesis and a deficit of exogenous arginine were possibly induced by Shikonin and further inhibit the viability of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine is essential for protein synthesis in adult mammals and plays multiple functions in cell activities. Based on the metabolic vulnerability in tumors, arginine deprivation therapies were developed recently through giving availability to arginine degrading enzymes 18 . In the present study, arginine in mice serum was down-regulated suggesting that the impairment in arginine synthesis and a deficit of exogenous arginine were possibly induced by Shikonin and further inhibit the viability of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that tumor invasiveness and aggressiveness are highly dependent on malignant cell motility. A negative impact of arginine deprivation as a monotreatment on the motility of glioblastoma, melanoma and colon carcinoma cells was observed [ 25 , 45 , 70 ]. This phenomenon in glioblastoma cells was most probably evoked by the decrease in the content of the positively charged arginylated form of β-actin and polymerized F-actin [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with the toxin, cells exhibited an increase in adhesion as shown in the adhesion assay. We have previously shown that overexpression of RhoA leads to an increase in cell adhesion in breast cancer cells, among other tumor types (28,29,(38)(39)(40)(41). RhoA regulates focal adhesion dynamics via its downstream effector Rho-associated protein kinase 1 and the formation of stress fibers needed for migration (28,(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%